COLLABORATIVE ORGANIZATIONAL DEVELOPMENT MODEL FOR EFFECTIVE SMK–INDUSTRY LINK AND MATCH: SYSTEMATIC REVIEW - Abdul Marta Nurdin; Sholeh Hidayat; Lukman Nulhakim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The gap between vocational education graduates’ competencies and industry needs remains a major challenge in achieving effective link and match between schools and the workplace. This study aims to develop a collaboration-based organizational development model to strengthen partnerships between vocational high schools and industry within the context of Technical and Vocational Education and Training (TVET). The study employed a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected from the Scopus and Publish or Perish (PoP) databases using keywords related to TVET organizational development, school–industry partnerships, and work-based learning. The selection process involved identification, screening, eligibility, and inclusion stages. Of the 81 articles initially identified, 20 articles met the inclusion criteria and were analyzed. The findings indicate that effective school–industry alignment is influenced by clear organizational structures, collaborative leadership, open organizational culture, the capacity of teachers and industry mentors, curriculum integration, collaborative assessment practices, and sustainable monitoring and evaluation systems. The study concludes that collaboration-based organizational development is an effective strategy for improving vocational education quality, strengthening school–industry partnerships, and enhancing graduates’ employability. The proposed model provides a conceptual contribution to reinforcing the implementation of link and match within Technical and Vocational Education and Training (TVET). ABSTRAK Kesenjangan antara kompetensi lulusan pendidikan vokasi dan kebutuhan dunia industri masih menjadi tantangan dalam mewujudkan efektivitas hubungan dan kesesuaian (link and match) antara sekolah dan dunia kerja. Penelitian ini bertujuan mengembangkan model pengembangan organisasi berbasis kolaborasi yang dapat memperkuat kemitraan antara Sekolah Menengah Kejuruan (SMK) dan industri dalam konteks Technical and Vocational Education and Training (TVET). Penelitian menggunakan metode Systematic Literature Review (SLR) dengan mengikuti pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Data diperoleh dari basis data Scopus dan Publish or Perish (PoP) menggunakan kata kunci yang berkaitan dengan pengembangan organisasi TVET, kemitraan sekolah–industri, dan pembelajaran berbasis kerja. Proses seleksi dilakukan melalui tahap identifikasi, penyaringan, kelayakan, dan inklusi. Dari 81 artikel yang teridentifikasi, diperoleh 20 artikel yang memenuhi kriteria untuk dianalisis. Hasil kajian menunjukkan bahwa keberhasilan hubungan dan kesesuaian antara sekolah dan industri dipengaruhi oleh struktur organisasi yang jelas, kepemimpinan kolaboratif, budaya organisasi yang terbuka, peningkatan kapasitas guru dan mentor industri, integrasi kurikulum, praktik penilaian kolaboratif, serta sistem pemantauan dan evaluasi yang berkelanjutan. Temuan penelitian menunjukkan bahwa pengembangan organisasi berbasis kolaborasi merupakan strategi yang efektif untuk meningkatkan kualitas pendidikan vokasi, memperkuat kemitraan sekolah–industri, dan meningkatkan kesiapan kerja lulusan. Model yang dihasilkan memberikan kontribusi konseptual bagi penguatan implementasi link and match dalam pendidikan dan pelatihan kejuruan.